Exegetical commentary on the Old Testament: Ruth a discourse analysis of the Hebrew Bible - Block, Daniel Isaac, 1943- (2015)
Ruth is widely recognized as a superlative literary achievement of ancient Israel. With its sensitive portrayal of women in crisis, its admiration for a righteous man, and its profound theology of providence it offers hearers in every age a window into life in the ancient Near East, inspiration for good and godly living, and reason to wonder at the common roots of Israel's royal and messianic hope. Bridging the historical and theological gap between Judges and Samuel, the book of Ruth explains specifically first how David, the most important character in the Hebrew Bible, could emerge from the spiritual and ethical morass of the premonarchic period, and second to account for the Moabite blood in this king's veins. - Back cover.
Series introduction -- Author's preface and acknowledgments -- Abbreviations -- Select bibliography -- Translation of Ruth -- Introduction to Ruth -- Commentary on Ruth -- Appendix : A dramatic reading of the Book of Ruth -- Scripture index -- Subject index -- Author index.
Includes bibliographical references (pages 19-21) and indexes.
Keywords: Bible. -- Commentaries; Commentaries